User involvement method in the early stage of new product development process for successful product - Alli, Hassan (Faculty of Design & Architecture, Universiti Putra Malaysia, 2018)
User involvement in the early stage of product development process is often increase the innovative of product ideas and as well as facilitate the product designer to establish the characteristics of a new product. A number of methods were used to incorporate the user knowledge in the early stage of a new product development process. Many new strategies were introduced for a systematic and efficiency planning to deliver a better product outcome. However, the product developers are facing difficulties with developing new strategies for a successful product. Whilst, the successful rate of new products still issues and discussing among them. Thus, this study is proposed to identify an effective user involvement method in the early stage of new product development in which contributed in the success of a product. A structured interview was conducted through face-to-face interview with twenty-seven (27) respondents known as product management specialist. The result given a strong recommendation to the well-organized user involvement in the early stage of product development process and significantly in product definition stage. In addition, the identified and selected method is used to increase the design process performance and support the likelihood of successful a new product.